2021
DOI: 10.1016/j.jad.2020.09.130
|View full text |Cite
|
Sign up to set email alerts
|

Does premenstrual syndrome before pregnancy increase the risk of postpartum depression? Findings from the Australian Longitudinal Study on Women's Health

Abstract: BackgroundPrevious literature suggests a positive association between history of premenstrual syndrome (PMS) and development of postpartum depression (PPD); however, limited evidence has come from prospective population-based studies and whether history of depression affects this association is unknown. MethodsThis study included 5479 women from the 1973-78 cohort of the Australian Longitudinal Study on Women's Health and estimated the association between pre-pregnancy PMS and PPD. Participants were followed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…showing that there is a positive and significant relationship between PMS and postpartum depression. 6,28,29 Çoban et al 30 determined that the presence of PMS is among the factors affecting the development of postpartum depression. Maliszewska et al 31 found that a history of PMS was associated with a greater chance of depressive symptoms in the postpartum second month.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showing that there is a positive and significant relationship between PMS and postpartum depression. 6,28,29 Çoban et al 30 determined that the presence of PMS is among the factors affecting the development of postpartum depression. Maliszewska et al 31 found that a history of PMS was associated with a greater chance of depressive symptoms in the postpartum second month.…”
Section: Discussionmentioning
confidence: 99%
“…Because estrogen and progesterone regulate biological systems, neural networks, and behaviors associated with mood, changes in the levels of the two hormones can trigger depressive symptoms. Since the sudden drop in hormonal levels occurs in the luteal phase as well as after birth, women sensitive to hormonal fluctuations may have both PMS and postpartum depression 6 . Studies have reported that there is a strong relationship between the menstrual cycle and mood disorders that occur in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further research is needed to determine whether isoallopregnanolone, which antagonizes the effect of allopregnanolone on the GABA-A receptor, has the potential to become a treatment for PMDD 64 , 65 . The US Food and Drug Administration recently approved allopregnanolone itself (brexanolone) for the treatment of postpartum depression (PPD) 68 , 69 , a disorder extensively associated with PMS/PMDD 70 , 71 in the context of reproductive depression 72 . Exposure to high allopregnanolone levels during pregnancy has a protective and mood-stabilizing effect, while in susceptible women, the sudden decrease in allopregnanolone following placental detachment at birth alters the GABAergic signaling 73 76 .…”
Section: Neurotransmitters Hormones and Neurosteroidsmentioning
confidence: 99%
“…In recent years, increasing research further investigated the comorbidities of severe PMS/PMDD, and a strong association with psychiatric disorders was confirmed 12 , 137 . Women with severe PMS/PMDD are at higher risk to develop PPD 70 and suicide experiences 138 140 and manifest increased incidences of generalized anxiety disorder 141 , bipolar disorder 142 , eating disorders 143 , addictive behaviors such as nicotine or alcohol use 144 , and poor sleep quality 145 . Exposure to traumatic events, childhood physical and emotional abuse, and post-traumatic stress disorder also correlate with PMS/PMDD 146 148 .…”
Section: Other Trends In Researchmentioning
confidence: 99%